Large scale spatio-temporal forcing of pelagic-coastal coupling: disentangling the effects of environmental change on intertidal invertebrate recruitment - Muñiz, Carlota Fernández (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
Marine systems are driven by the relationships among organisms and environmental conditions. Anthropogenic-induced changes during the past decades have started to alter climatic drivers which have the potential to alter the physical, chemical and biological environment. In coastal systems, biogeography is influenced by the temporal variability in the conditions of the water mass. In addition, many marine benthic organisms develop in the water mass and rely on the conditions that link the pelagic and benthic systems for population maintenance. Such pelagic-coastal coupling indicates that changes in the trophic system during development can be transferred to the adult populations through changes in propagule supply. Thus, changes in environmental conditions can influence benthic populations directly (e.g. through larval advection) or indirectly, through their influence on the phytoplankton community (e.g. through the development of HABs). The South African coastline shows clear alongshore patterns of faunal biomass and species richness. On the south coast, strong longitudinal patterns of recruitment of intertidal organisms exist, with areas of particularly high recruitment. HABs of unprecedented spatio-temporal magnitude have recently developed along the south coast, including the areas where benthic recruitment is most intense. The present thesis used these blooms to study changes in intertidal recruitment directly or indirectly associated with their occurrence. Using a combination of remote sensing data to study the environmental conditions of the water mass in the innermost part of the Agulhas Bank, and estimates of mussel and barnacle recruitment rates to integrate the effects of conditions in the water mass during larval development, this thesis aimed to: (1) understand the conditions that triggered the development of an HAB of the dinoflagellate Lingulodinium polyedrum during summer of 2014, (2) determine the direct or indirect effects of that bloom on recruitment of intertidal organisms, and understand the factors that affect recruitment along the coast, (3) determine if the environmental factors during bloom development produced any carryover effects on recruit growth and mortality, and (4) determine the factors that drive changes in community biomass and composition along the south coast, the long-term trends in those factors, and possible changes experienced in recent years. Water column stability during spring, before the development of the red tide, followed by alternating periods of upwelling and relaxation during summer and autumn, seemed to promote the development and persistence of L. polyedrum. Recruitment of mussels and barnacles was estimated during the reproductive season of mussels in 2014, coinciding with the red tide, and during the following year. Alongshore patterns in recruitment were found, with higher mussel recruitment in the absence of the red tide and the opposite pattern in barnacles. Alongshore patterns in SST and chlorophyll matching those of recruitment were also found, with higher SSTs and lower chlorophyll during the red tide than the following year. Growth and mortality rates in barnacles did not differ between years during the first five months after settlement. This suggests that the factors which produced differences in recruitment between years did not produce carryover effects detectable at the temporal scales studied. Further analysis of 15 years of satellite-derived environmental data showed significant cooling trends potentially driven by a long-term seasonal acceleration of the Agulhas Current in autumn around two upwelling centres on the south coast, coinciding temporally with the reproductive period of mussels and barnacles, and spatially with the areas of highest recruitment. In addition, the comparison of SST and chl-a conditions during the first and the second half of the period of study showed that seasonality of both variables has changed in large areas over the shelf, with increasing importance of shorter-term variability, which would in turn decrease environmental predictability. Thus, the conditions observed during the present study, particularly during 2015, when upwelling seemed to be more intense, may presage the potential effects of identified long-term cooling trends at the upwelling centres. Although the general trend shows cooling around those areas, conditions can vary greatly among years, favouring different taxa. Changes in the Agulhas Current System are affected by changes in distant areas in the Indian Ocean basin. Such tele-connection is unlikely to be unique to this system and indicates the importance of understanding trends in major large scale climatic drivers and their regional effects in order to make predictions about coastal systems.
Keywords: Uncatalogued